Regional differences of the agricultural and rural development sector - Vincze, Mária; Mezei, Elemér; Marton, Györgyi (Acta Agraria Debreceniensis, 2012)
Is neccessary and possible to take in consideration the regional differences of agriculture- and rural development in the rural development program for period 2014–2020? For answer of this question we try to give some references by reveal of economic and social regional differences.